PENINGKATAN KEMAMPUAN MEMBACA MENULIS DAN BERHITUNG BAGI LANSIA DI PONDOK PESANTREN LANSIA SABILUNNAJAH SLEMAN YOGYAKARTA - Ari Bowo, Ahmad Nasir; Kusumawati, Intan; Putra, Aji Permana; Wahono, Joko (Gemi: Jurnal Penelitian dan Pengabdian, 2024)
Training to improve reading, writing and arithmetic skills for the elderly is located at the Sabilunnajah Elderly Islamic Boarding School, Sleman Regency, Yogyakarta Province. The problems of the elderly at the Sabilunnajah Islamic Boarding School include some elderly who do not graduate from elementary school, the elderly easily forget and do not understand the material, the limitations of the ustadz/ustadzah Pondok, there being no basic material for reading, writing and arithmetic. The aim of the training is to improve reading, writing and arithmetic skills for the elderly. Implementation of training a total of 8 times. The elderly students who took part in the training activities were 38 students. The results of the training show that there is an increase in reading, writing and arithmetic skills, namely 35%. Before the training, the average score for reading, writing, and arithmetic was 60%. After training increased to 95%.